2022
DOI: 10.3390/ani12080969
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon Insertion Polymorphisms (RIPs) in Pig Coat Color Candidate Genes

Abstract: The diversity of livestock coat color results from human positive selection and represents an indispensable part of breed identity. As an important biodiversity resource, pigs have many special characteristics, including the most visualized feature, coat color, and excellent adaptation, and the coat color represents an important phenotypic characteristic of the pig breed. Exploring the genetic mechanisms of phenotypic characteristics and the melanocortin system is of considerable interest in domestic animals b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The resulting fragments can be sequenced on an NGS platform to identify polymorphisms. Another NGS-based approach for studying TEs is the retrotransposon insertion polymorphisms (RIPs) technique ( Du et al., 2022 ), which uses PCR to amplify specific regions of the genome flanking retrotransposon insertions. The resulting fragments can be sequenced on an NGS platform to identify insertion and deletion events.…”
Section: Prospects Challenges and Discussionmentioning
confidence: 99%
“…The resulting fragments can be sequenced on an NGS platform to identify polymorphisms. Another NGS-based approach for studying TEs is the retrotransposon insertion polymorphisms (RIPs) technique ( Du et al., 2022 ), which uses PCR to amplify specific regions of the genome flanking retrotransposon insertions. The resulting fragments can be sequenced on an NGS platform to identify insertion and deletion events.…”
Section: Prospects Challenges and Discussionmentioning
confidence: 99%
“…Therefore, the true-melanogenesis operating mechanism should be initiated by melanosome formation and adding to genes associated with coat color (Moreiras et al 2021). Furthermore, during melanosome biogenesis, numerous molecules are involved in intracellular trafficking (Du et al 2022).…”
Section: The Potential Association Between the Mc1r Gene And The Coat...mentioning
confidence: 99%
“…Local pigs have diverse coat color phenotypes, including black, red, white, spotted, brown, belted, and two-end black, resulting from an artificial selection over an extended period (Wu et al 2019). Several important genes affecting pig coat color phenotypes have been identified to date, including mast/ stem-cell growth factor receptor (KIT), Melanocyte Inducing Transcription Factor (MITF), antagonist Agouti Signaling Protein (ASIP), DCT, Tyrosinase-related Protein 1 (TYRP1) (Du et al 2022). Melanocortin 1 Receptor (MC1R) gene determines dominant black, black-spotted, and red coat colors in Western and Chinese pigs (Zhong et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of dilution of the dog's coat color will be affected by inserting the SINE retrotransposon into the exon of the PMEL gene Three SINE Insertion Polymorphic Sites were Identified in Insulin-like Growth Factor 2 mRNA-binding Proteins (Murphy et al 2018). Diverse mutations (SNPs) within MC1R, TYRP1, ASIP genes have been reported and they may be associted with phenotypes of coat color in wild pigs (Yang et al 2019), furthermore, at least 40 RIPs in coat color genes have been reported and some RIPs may be associated with the coat color differences between different domesticated pig breeds (Du et al 2022).…”
Section: Introductionmentioning
confidence: 99%